Perancangan Brand Campaign untuk Meningkatkan Brand Awareness Pickyourstyle.ind - Onggowarsito, Everine Joana Onggowarsito (Universitas Ciputra Surabaya, 2024)
Fashion serves not only as a means of covering the body but also as a tool for communication and expression of identity. Many individuals struggle to express themselves through clothing due to a lack of confidence, concern for others' opinions, and limitations in finding models and sizes that align with their preferences. Pickyourstyle.ind is a fashion business specializing in unisex leather clothing, offering outerwear, tops, and bottoms in various colors and designs. Despite its establishment in 2021, Pickyourstyle.ind has not garnered sufficient awareness from the public. Therefore, this research aims to design a brand campaign for Pickyourstyle.ind along with its promotional media to enhance brand awareness. The research methodology involves collecting both qualitative and quantitative primary data, as well as secondary data. Qualitative methods include interviews with expert and extreme users, while quantitative methods involve distributing surveys through Google Forms. This design process is supported by the collection of secondary data from literature such as books and journals. The outcome of this design is the 'Express Yourself' brand campaign, comprising various promotional campaign design media and content on social media platforms like Instagram and TikTok. The final design of the promotional media includes informative and engaging content on Instagram feeds, interactive quiz content on Instagram stories, and interactive videos on TikTok and Reels.